Surface pH buffering to promote degradation of mesoporous silica nanoparticles under a physiological condition - Choi, Eunshil; Kim, Sehoon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Despite significant advancement of mesoporous silica nanoparticle (MSN)-based biomedical research, studies have not been done enough to understand biodegradability of functional MSNs for better clinical efficacy. Polyethyleneimine (PEI) is one of the mostly used surface functionalities of MSNs, owing to the amine-rich chemical composition and the well-known proton sponge effect. In this paper, we study degradation behaviors of PEI-coated MSNs (PEI-MSNs) under a neutral or acidic physiological condition in comparison to those of surface-uncoated or nonionic F-127-encapsulated MSNs. The results showed that the surface coating by PEI could promote particle degradation in both neutral and acidic phosphate buffered saline (PBS) solution (i.e., pH 7.4 and 5.0). Importantly, we demonstrated that the local pH buffering by the surface PEI could lead to a greater total degradation quantity of particles even in the acidic PBS solution. The PEI-induced pH buffering phenomenon was confirmed by using a fluorescent pH indicator dye, fluorescein, which was attached to the surface of PEI-MSNs (F-PEI-MSNs). The observed pH-insensitive fluorescing behavior of fluorescein attained by surface coating with PEI corroborates the buffering effect that minimizes the surface pH change regardless of the external pH. The presented results may offer a useful insight into the degradability of silica nanomaterials with PEI or related surface functionalities, especially in the acidic subcellular microenvironment. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: DELIVERY-SYSTEMS; SIZE; BEHAVIOR; RELEASE; SPHERES; GROWTH; PGMAS